Strategy Set-Shifting and Response Inhibition in Adult Rats Exposed to an Environmental Polychlorinated Biphenyl Mixture during Adolescence - Monaikul, Supida (Neurotoxicol Teratol, 2017)
Converging evidence from studies with animal models and humans suggests that early developmental exposure to polychlorinated biphenyls (PCBs) leads to deficits in cognitive flexibility and inhibitory control. These processes are mediated to a large extent by the prefrontal cortex, thus we examined the effects of PCB exposure during adolescence—a period of robust prefrontal cortical development—on both processes. Specifically, we used operant set-shifting and differential reinforcement of low rates of responding (DRL) tasks to assess cognitive flexibility and response inhibition, respectively. One male and one female pup from each of 14 litters were assigned to each of three treatment groups: 0, 3 or 6 mg PCB/kg/day. Rats were dosed orally from postnatal day (PND) 27–50 to capture the whole period of adolescence in rats. At approximately PND 90, they began testing in the set-shifting task which included an initial visual cue discrimination, an extra-dimensional shift to a position discrimination and a reversal of the position discrimination. There were no statistically significant group differences in errors to criterion on visual cue discrimination or on the shift from visual to position discrimination in either males or females. During the position reversal, the 6 mg/kg PCB males made significantly fewer errors to reach criterion than control males. The 3 mg/kg PCB males showed a trend in the same direction, but this did not reach statistical significance. Interestingly, error analysis revealed that PCB-exposed males made significantly fewer perseverative errors than controls in this phase. No group differences were observed in females. These results suggest a male-specific effect of adolescent PCB-exposure on the reversal phase of the set-shifting task. Following set-shifting, rats progressed to the DRL task in which they were required to withhold responding for a specified period of time (15 seconds) in order to receive a reinforcer. There were no exposure-related group differences in total presses or efficiency ratio in males or in females. In summary, there were subtle sex-specific effects of adolescent PCB exposure on the reversal phase of a set-shifting task, but no effects of exposure on performance on a DRL15 task, suggesting an effect on cognitive flexibility but not response inhibition.